Evaluation of the effect of Matricaria recutita monotherapy or in combination with photodynamic therapy on tissue repair in the dorsum of the tongue of rats* - Juliana Borges de Lima DANTAS; Tila FORTUNA; Hortência Resende DELLA CELLA; Fábio Luís Meneses de Sousa da SILVA; Rejane Conceição SANTANA; Gabriela Botelho MARTINS (University of São Paulo, 2023)
Abstract The search for treatments that accelerate the healing of lesions is of constant interest. Matricaria recutita (chamomile) is a plant with antimicrobial, anti-inflammatory, and healing properties, and antimicrobial Photodynamic Therapy (aPDT) eradicates microorganisms, which favors tissue repair. Objective This study aimed to evaluate the effect of the topical use of chamomile with or without aPDT on tissue repair in rats' tongues. Methodology A total of 75 male Wistar rats underwent standardized ulceration on the dorsum of the tongue using a punch of 5 mm diameter and were randomly allocated into the following groups: control (G1), chamomile fluid extract (G2), chamomile infusion (G3), aPDT (G4), and chamomile infusion + aPDT (G5). On the 3rd, 7th, and 14th days postoperatively, euthanasia was performed, and the ulcers were measured using calipers. The presence of edema, inflammatory infiltrate, cellularity, re-epithelialization, and characterization of total collagen were evaluated using sections stained with Hematoxylin and Eosin and Red Sirius. Histomorphometry analyses of the percentage of total collagen, the distance from the basal layer to the epithelial surface, and the thickness of the stratum corneum were performed. Descriptive (absolute/relative frequencies and modes) and exploratory analyses were performed. The associations between the groups and the presence of ulcers were analyzed with Fisher's exact test. All analyses were performed using the R program and statistical significance was set at p=0.05. Results The G2 positively modulated the exudative and proliferative phases of repair, both clinically (p<0.0001) and histologically, whether in descriptive or inferential analyses (p<0.05). The G3 showed a significant difference in clinical parameters compared with G1 (p<0.0001). The G4 and G5 did not positively modulate tissue repair. Conclusion The chamomile fluid extract showed better outcomes for tissue repair in the rat tongue.